Drought analysis using the standardized precipitation index (SPI) - Šebenik, Urša (Acta geographica Slovenica, 2017)
Drought indices are commonly used for detection, monitoring and evaluation of drought events. One of the most commonly used drought indices is the Standardized Precipitation Index (SPI). This paper presents the effect of theoretical distribution selection on SPI values, and the analysis of drought events for five selected meteorological stations in Slovenia. We found that the SPI on the annual time scale shows a similar pattern of occurrence of dry and wet periods at Ljubljana-Bežigrad, Novo mesto, and Trieste meteorological stations; something similar can be said for the Celje and Maribor-Tabor stations. The analysis of the correlations between the standardized data river discharge and precipitation data for the selected river basin of the River Pesnica shows the strongest correlation between the SPI-2 and standardized disDrought indices are commonly used for detection, monitoring and evaluation of drought events. One of the most commonly used drought indices is the Standardized Precipitation Index (SPI). This paper presents the effect of theoretical distribution selection on SPI values, and the analysis of drought events for five selected meteorological stations in Slovenia. We found that the SPI on the annual time scale shows a similar pattern of occurrence of dry and wet periods at Ljubljana-Bežigrad, Novo mesto, and Trieste meteorological stations; something similar can be said for the Celje and Maribor-Tabor stations. The analysis of the correlations between the standardized data river discharge and precipitation data for the selected river basin of the River Pesnica shows the strongest correlation between the SPI-2 and standardized dischargescharges
Keywords: climate; klimatski ekstremi; padavine; podnebje; Slovenia; Slovenija; suša